The Chaperone TRAP1 As a Modulator of the Mitochondrial Adaptations in Cancer Cells - Masgras, Ionica; Sanchez-Martin, Carlos; Colombo, Giorgio; Rasola, Andrea (Frontiers in Oncology, 2017)
Mitochondria can receive, integrate and transmit a variety of signals in order to shape many biochemical activities of the cell. In the process of tumor onset and growth, mitochondria contribute to the capability of cells of escaping death insults, handling changes in ROS levels, rewiring metabolism and reprograming gene expression. Therefore, mitochondria can tune the bioenergetic and anabolic needs of neoplastic cells in a rapid and flexible way, and these adaptations are required for cell survival and proliferation in the fluctuating environment of a rapidly growing tumor mass. The molecular bases of pro-neoplastic mitochondrial adaptations are complex and only partially understood. Recently, the mitochondrial molecular chaperone TRAP1 (tumor necrosis factor receptor-associated protein 1) was identified as a key regulator of mitochondrial bioenergetics in tumor cells, with a profound impact on neoplastic growth. In this review we analyze these findings and discuss the possibility that targeting TRAP1 constitutes a new anti-tumor approach.